Warming and acidification shape zooplankton community dynamics in Jiaozhou Bay: evidence from an Acid-Heat Vector Intensity Index - Jinchang Sui; Yuqiu Wei; Zhengguo Cui; Haoyu Jin; Chuanxia Liu; Keming Qu; Dongsheng Ding (Marine Pollution Bulletin, 2026)

Antagonistic effects of temperature and salinity on total dimethylsulfoniopropionate (DMSPt) production in a river-dominated bay during extreme winter events - Lingxiao Li; Jing Sun; Zhengguo Cui; Tao Jiang; Zhenhao Liu; Keming Qu; Hongsheng Wang; Qingjing Hu; Hongwu Cui; Shenghui Zhang (Estuarine, Coastal and Shelf Science, 2026)

Environmental controls and nonlinear responses of the diatom-dinoflagellate ratio in Jiaozhou Bay - Yipeng Huang; Zhengguo Cui; Changhua Liu; Dongsheng Ding; Lin Zhu; Keming Qu; Yuqiu Wei; Jun Sun (Marine Pollution Bulletin, 2026)

From protein-like to humic-like substances: Feed-derived regulation of dissolved organic matter transformation in RAS - Ying Bai; Ruijie Ma; Zhengguo Cui; Hao Li; Hongwu Cui; Yong Xu; Jianlei Chen; Keming Qu (Aquacultural Engineering, 2026)

Unveiling the mechanism: DOM from chemically pretreated corncobs drives denitrification via mediating microbial community succession - Ying Bai; Ruijie Ma; Zhengguo Cui; Hongwu Cui; Weiman Gong; Wei Dong; Hao Li; Yong Xu; Jianlei Chen; Keming Qu (Journal of Environmental Chemical Engineering, 2026)

Adaptation Mechanisms of Aquatic Animals to Saline–Alkaline Water Aquaculture: Physiological, Energetic and Molecular Perspectives - Yingsha Qu; Huichen Li; Bo Zhang; Hongwu Cui; Jianlei Chen; Yong Xu; Zhengguo Cui; Keming Qu; Hao Li (Fishes, 2026)
Saline–alkaline water constitutes a vital strategic non-traditional fishery resource in China, characterized by high pH values, elevated carbonate alkalinity, and complex ionic compositions. These extreme environmental conditions impose significant stress on aquatic animals, mainly by inducing ionic toxicity and disrupting acid–base regulatory mechanisms. Such disruptions subsequently lead to osmotic imbalance, metabolic dysregulation, and immunosuppression, thus restricting the survival and growth of aquatic species in aquaculture systems. Consequently, the sustainable development of the saline–alkaline aquaculture is imperative for enhancing production efficiency and promoting the utilization of marginal land and water resources. This review comprehensively summarizes the current status of saline–alkaline aquaculture and highlights the stress-inducing impacts of salinity, alkalinity, and specific ionic ratios on teleost fishes and crustaceans. It further explores key adaptive mechanisms, including osmoregulatory and ionoregulatory strategies, bioenergetic trade-offs related to oxygen consumption and ammonia excretion, coordinated antioxidant and innate immune responses, as well as recent findings from multi-omics research. This review aims to offer a scientific foundation for the selection and breeding of saline–alkaline-tolerant strains, the precise regulation of aquaculture water environments, and the development of ecological aquaculture models in saline–alkaline regions, thereby facilitating the sustainable utilization of saline–alkaline land and water resources.

Optimizing shrimp growth and water quality in constructed wetland recirculating aquaculture systems: Effects of stocking density and shrimp size - Meimei Hu; Yanyan Wang; Jianlei Chen; Hongwu Cui; Shengmin Zhu; Tongtong Jin; Keming Qu; Zhengguo Cui (Aquaculture, 2026)

Significant effects of temperature and pH on zooplankton dynamics: Implications for ocean warming and acidification - Minghao Li; Dongsheng Ding; Chuanxia Liu; Zhengguo Cui; Wei Dong; Jun Sun; Keming Qu; Yuqiu Wei (Ocean & Coastal Management, 2026)

Hematotoxicity of Fe- and Cr-based metal–organic framework nanoparticles in rockfish Sebastes schlegelii - Yiling Li; Junyu Ye; Meiyu Wang; Yang Gao; Bin Xia; Zhengguo Cui; Keming Qu (Marine Environmental Research, 2026)

Waterborne and dietary accumulation and toxicity of iron-based metal-organic framework in cladoceran Moina mongolica Daday - Yiling Li; Zihan Liu; Zhengguo Cui; Keming Qu; Bin Xia (Journal of Hazardous Materials, 2025)

Carnitine content and its influencing factors in marine animals collected from China’s offshore region and the Northwest Pacific Ocean - Yufeng Gao; Zhengguo Cui; Jianwei Li; Keming Qu; Qingkui Wang; Lanlan He; Xiangtao Liu; Xiner Zhao; Liuyizhi Zhang; Lingxiao Li; Ying Bai; Fangqun Dai; et al. (Acta Oceanologica Sinica, 2025)

Impact of Water Velocity on Litopenaeus vannamei Behavior Using ByteTrack-Based Multi-Object Tracking - Jiahao Zhang; Lei Wang; Zhengguo Cui; Hao Li; Jianlei Chen; Yong Xu; Haixiang Zhao; Zhenming Huang; Keming Qu; Hongwu Cui (Fishes, 2025)
In factory-controlled recirculating aquaculture systems, precise regulation of water velocity is crucial for optimizing shrimp feeding behavior and improving aquaculture efficiency. However, quantitative analysis of the impact of water velocity on shrimp behavior remains challenging. This study developed an innovative multi-objective behavioral analysis framework integrating detection, tracking, and behavioral interpretation. Specifically, the YOLOv8 model was employed for precise shrimp detection, ByteTrack with a dual-threshold matching strategy ensured continuous individual trajectory tracking in complex water environments, and Kalman filtering corrected coordinate offsets caused by water refraction. Under typical recirculating aquaculture system conditions, three water circulation rates (2.0, 5.0, and 10.0 cycles/day) were established to simulate varying flow velocities. High-frequency imaging (30 fps) was used to simultaneously record and analyze the movement trajectories of Litopenaeus vannamei during feeding and non-feeding periods, from which two-dimensional behavioral parameters—velocity and turning angle—were extracted. Key experimental results indicated that water circulation rates significantly affected shrimp movement velocity but had no significant effect on turning angle. Importantly, under only the moderate circulation rate (5.0 cycles/day), the average movement velocity during feeding was significantly lower than during non-feeding periods (p

Functionalization-dependent toxicity of MIL-101 metal-organic frameworks to phytoplankton Chlamydomonas reinhardtii - Meiyu Wang; Bin Xia; Zhengguo Cui; Keming Qu; Yiling Li (Aquatic Toxicology, 2025)

The Application of Digital Twin Technology in the Development of Intelligent Aquaculture: Status and Opportunities - Jianlei Chen; Yong Xu; Hao Li; Xinguo Zhao; Yang Su; Chunhao Qi; Keming Qu; Zhengguo Cui (Fishes, 2025)
Aquaculture is vital for global food security but faces challenges like disease, water quality control, and resource optimization. Digital twin technology, a real-time virtual replica of physical aquaculture systems, emerges as a transformative solution. By integrating sensors and data analytics, it enables monitoring and optimization of water quality, feed efficiency, fish health, and operations. This review explores the current adoption status of digital twins in aquaculture, highlighting applications in real-time monitoring and system optimization. It addresses key implementation challenges, including data integration and scalability, and identifies emerging opportunities for advancing sustainable, intelligent aquaculture practices.

Significance of temperature and salinity in the dynamics of diatoms and dinoflagellates along the coastal Yellow Sea - Chenshi Weng; Dongsheng Ding; Qian Yang; Lin Zhu; Jun Sun; Keming Qu; Zhengguo Cui; Yuqiu Wei (Progress in Oceanography, 2025)

Network pharmacology, molecular docking, molecular dynamics simulation, and experiment verification analysis to reveal the action mechanism of RenShen Guipi Wan in the treatment of anemia - Tingli Qu; Nan Zhang; Chen Li; Xuyuan Liu; Keming Yun; Quan An (Biotechnology Letters, 2025)

Sedimentary heavy metal interactions with phytoplankton and zooplankton across the Bohai Sea - Yuqiu Wei; Lun Song; Yuanqing Ma; Jiandong Mu; Wei Yi; Jun Sun; Keming Qu; Zhengguo Cui (Journal of Environmental Management, 2025)

Implications of seawater characteristics on dissolved heavy metals in near-shore surface waters of the Yellow Sea - Minghao Li; Dongsheng Ding; Yong Xu; Qian Yang; Jun Sun; Keming Qu; Zhengguo Cui; Yuqiu Wei (Marine Pollution Bulletin, 2025)

Ecological risk assessment for BDE-47 in marine environment based on species sensitivity distribution method - Ying Bai; Ruijie Ma; Zhengguo Cui; Liping Liu; Dongsheng Ding; Qingjing Hu; Bin Xia; Zhaochuan Li; Haibo Zhang; Keming Qu (Marine Environmental Research, 2025)

Effects of heavy metal concentration on zooplankton community composition and abundance in the Yellow Sea coast - Chenshi Weng; Dongsheng Ding; Zhengguo Cui; Keming Qu; Yuqiu Wei; Haiyan Hu (Marine Environmental Research, 2025)

Optical characteristic of dissolved organic matter polar fractions by spectrum technologies and the relationship with indirect photodegradation of ofloxacin - Shukai Liu; Zhengguo Cui; Ying Bai; Dongsheng Ding; Qingjing Hu; Yuqiu Wei; Lin Zhu; Keming Qu; Rongguo Su (Journal of Environmental Chemical Engineering, 2024)

Early warning system for nocardiosis in largemouth bass (Micropterus salmoides) based on multimodal information fusion - Zhenming Huang; Haixiang Zhao; Zhengguo Cui; Lei Wang; Hao Li; Keming Qu; Hongwu Cui (Computers and Electronics in Agriculture, 2024)

Purification of seawater aquaculture using constructed wetlands in a recirculating aquaculture system for Pacific white shrimp (Litopenaeus vannamei) and analysis of microbial community structure - Yanyan Wang; Meimei Hu; Jianlei Chen; Hongwu Cui; Shengmin Zhu; Tongtong Jin; Keming Qu; Zhengguo Cui (Journal of Water Process Engineering, 2024)

Implications of ocean warming and acidification on heavy metals in surface seawater of the Bohai Sea - Yuqiu Wei; Lun Song; Yuanqing Ma; Jiandong Mu; Wei Yi; Jun Sun; Keming Qu; Zhengguo Cui (Journal of Hazardous Materials, 2024)

Effect of hydraulic retention time on denitrification performance and microbial communities of solid-phase denitrifying reactors using polycaprolactone/corncob composite - Hongwu Cui; Yuna Feng; Weibin Lu; Lu Wang; Hao Li; Yu Teng; Ying Bai; Keming Qu; Yingying Song; Zhengguo Cui (Marine Pollution Bulletin, 2024)

Bioaccumulation of polycyclic aromatic hydrocarbons and their human health risks depend on the characteristics of microplastics in marine organisms of Sanggou Bay, China - Qi Sui; Xiaobin Yang; Xuemei Sun; Lin Zhu; Xinguo Zhao; Zhihua Feng; Bin Xia; Keming Qu (Journal of Hazardous Materials, 2024)

A comparative analysis of growth and nutritional quality of the hybrid grouper (Epinephelus fuscoguttatus ♀ × Epinephelus lanceolatus ♂) in a simulated pond system and a recirculating aquaculture system - Yingsha Qu; Zhendong Yin; Xiangyu Fan; Haiyan Hu; Hongwu Cui; Zhengguo Cui; Keming Qu; Hao Li (Frontiers in Marine Science, 2024)
Groupers, as a popular economic fish species, are now more frequently cultured in land-based facilities, however, traditional pond-farming methods are plagued by frequent disease outbreaks, unstable economic benefits, and environmental pollution. To explore a new farming mode for a grouper, an 80-day cultivation experiment was conducted using both a simulated pond system (SPS) and a recirculating aquaculture system (RAS). The research aims to evaluate the growth performance, health (pathogenic bacteria, intestinal microbiota), off-flavor compounds (geosmin, 2-methylisoborneol), and nutritional component (amino acids, fatty acid composition and content) of a hybrid grouper ( Pinephelus fuscoguttatus ♀ × Epinephelus lanceolatus ♂ ) under different aquaculture systems. The results showed that the hybrid grouper in a RAS exhibited better growth performance; the concentration of Vibrio in the fish tissue in the RAS was significantly lower than that in the SPS. Moreover, the content of fresh amino acids in the RAS was significantly higher, and the levels of saturated fatty acids (SFAs) and ω-6 polyunsaturated fatty acids (ω-6PUFAs) were significantly higher in the RAS. This finding indicates the superior flavor and nutritional value of the grouper. These results prove that the RAS is suitable for the widespread cultivation of grouper.

Temperature and nutrients drive distinct successions between diatoms and dinoflagellates over the past 40 years: Implications for climate warming and eutrophication - Yuqiu Wei; Qingshan Luan; Xiujuan Shan; Hongwu Cui; Keming Qu; Zhengguo Cui; Jun Sun (Science of The Total Environment, 2024)

Environmental controls on the seasonal variations of diatoms and dinoflagellates in the Qingdao coastal region, the Yellow Sea - Qingxuan Wang; Qian Yang; Lin Zhu; Zhengguo Cui; Keming Qu; Yuqiu Wei (Marine Environmental Research, 2024)

Coastal ecological security assessment in Laizhou Bay, China: from the perspective of demographic-social-economic-natural complex ecosystem - Zhanying Wang; Meng Zhang; Zhengguo Cui; Yuqiu Wei; Ying Bai; Keming Qu (Environmental Science and Pollution Research, 2024)

Vision-based dual network using spatial-temporal geometric features for effective resolution of fish behavior recognition with fish overlap - Haixiang Zhao; Yuankai Wu; Keming Qu; Zhengguo Cui; Jianxin Zhu; Hao Li; Hongwu Cui (Aquacultural Engineering, 2024)

A fish appetite assessment method based on improved ByteTrack and spatiotemporal graph convolutional network - Haixiang Zhao; Hongwu Cui; Keming Qu; Jianxin Zhu; Hao Li; Zhengguo Cui; Yuankai Wu (Biosystems Engineering, 2024)

Physiological and transcriptomic analysis reveals the toxic and protective mechanisms of marine microalga Chlorella pyrenoidosa in response to TiO2 nanoparticles and UV-B radiation - Lin Zhu; Sulan Feng; Yu Li; Xuemei Sun; Qi Sui; Bijuan Chen; Keming Qu; Bin Xia (Science of The Total Environment, 2024)

Polystyrene nanoplastics affected the nutritional quality of Chlamys farreri through disturbing the function of gills and physiological metabolism: Comparison with microplastics - Yejiao Sun; Xinguo Zhao; Qi Sui; Xuemei Sun; Lin Zhu; Andy M. Booth; Bijuan Chen; Keming Qu; Bin Xia (Science of The Total Environment, 2024)

Environmental forcing of phytoplankton carbon-to-diversity ratio and carbon-to-chlorophyll ratio: A case study in Jiaozhou Bay, the Yellow Sea - Yingzhe Wang; Zhengguo Cui; Dongsheng Ding; Qian Yang; Lin Zhu; Keming Qu; Jun Sun; Yuqiu Wei (Marine Pollution Bulletin, 2023)

The characteristics of trimethylamine N-oxide content in different classes of marine animals over the coastal and offshore areas of China - Ning An; Hongsheng Wang; Jianwei Li; Lanlan He; Yufeng Gao; Lingxiao Li; Qingkui Wang; Zhengguo Cui; Keming Qu; Qingjing Hu (Marine Pollution Bulletin, 2023)

New insights into the impact of polystyrene micro/nanoplastics on the nutritional quality of marine jacopever (Sebastes schlegelii) - Xuemei Sun; Xuru Wang; Andy M. Booth; Lin Zhu; Qi Sui; Bijuan Chen; Keming Qu; Bin Xia (Science of The Total Environment, 2023)

Effect of the molecular weight of DOM on the indirect photodegradation of fluoroquinolone antibiotics - Shukai Liu; Zhengguo Cui; Dongsheng Ding; Ying Bai; Jianlei Chen; Hongwu Cui; Rongguo Su; Keming Qu (Journal of Environmental Management, 2023)

Identifying the key factors affecting the trimethylamine N-oxide content of teleost fishes collected from the marginal seas of China and the epipelagic zone of the northwest Pacific Ocean - Qingjing Hu; Wanyu Zhao; Keming Qu; Ning An; Lingxiao Li; Yuqiu Wei; Ying Bai; Tao Jiang; Jufa Chen; Fangqun Dai; Hongsheng Wang; Zhengguo Cui (Science of The Total Environment, 2023)

Spatial distribution and potential ecological risk assessment of heavy metals in the sediments of fishing ports along the coasts of the Yellow Sea and Bohai Sea - Hongsheng Wang; Qingjing Hu; Dongsheng Ding; Lingxiao Li; Ning An; Keming Qu; Chuanxia Liu; Mingying Zhou; Zhengguo Cui (Marine Pollution Bulletin, 2023)

High dimethylsulfoniopropionate concentrations in the surface seawater over the marginal seas of China and the Northwest Pacific Ocean during May–July of 2021 following La Niña - Lingxiao Li; Zhengguo Cui; Keming Qu; Hongsheng Wang; Ruohan Song; Xiaoke Hu; Shenghui Zhang; Tao Jiang; Mingying Zhou; Qingjing Hu (Marine Pollution Bulletin, 2023)

Contrasting currents drive geographic variability in the biomass of Pacific saury (Cololabis saira), zooplankton, and phytoplankton in the northwestern Pacific - Yuqiu Wei; Zhengguo Cui; Yongqiang Shi; Xiujuan Shan; Bingzhang Chen; Keming Qu; Quandong Xin; Tao Jiang; Jufa Chen (Progress in Oceanography, 2023)

Picocyanobacteria–A non-negligible group for the export of biomineral silica to ocean depth - Yuqiu Wei; Keming Qu; Zhengguo Cui; Jun Sun (Journal of Environmental Management, 2023)

Key determinants controlling the seasonal variation of coastal zooplankton communities: A case study along the Yellow Sea - Yuqiu Wei; Xueyang Chen; Ying Liu; Yingzhe Wang; Keming Qu; Jun Sun; Zhengguo Cui (Marine Pollution Bulletin, 2023)

The characteristics of CDOM structural composition and the effect on indirect photodegradation of sulfamerazine - Ying Bai; Zhengguo Cui; Dongsheng Ding; Chenfei Hong; Hongwu Cui; Qingjing Hu; Mingying Zhou; Keming Qu (Science of The Total Environment, 2023)

Ocean acidification enhances the embryotoxicity of CuO nanoparticles to Oryzias melastigma - Hao Wang; Qi Sui; Jian Zhao; Xuemei Sun; Lin Zhu; Bijuan Chen; Keming Qu; Bin Xia (Journal of Hazardous Materials, 2023)

Hazardous substances and their removal in recirculating aquaculture systems: A review - Hao Li; Zhengguo Cui; Hongwu Cui; Ying Bai; Zhendong Yin; Keming Qu (Aquaculture, 2023)

Charge-dependent negative effects of polystyrene nanoplastics on Oryzias melastigma under ocean acidification conditions - Yufei Chen; Xia Wang; Qi Sui; Guozhu Chang; Xuemei Sun; Lin Zhu; Bijuan Chen; Keming Qu; Bin Xia (Science of The Total Environment, 2023)

Indirect photodegradation of ofloxacin in simulated seawater: Important roles of DOM and environmental factors - Shukai Liu; Zhengguo Cui; Ying Bai; Dongsheng Ding; Junshuang Yin; Rongguo Su; Keming Qu (Frontiers in Marine Science, 2023)
Dissolved organic matter (DOM) plays a non-negligible role in the indirect photodegradation of organic contaminants. This research investigated the roles of DOM and the environmental factors (salinity, pH, NO 3 − , and HCO 3 − ) in the indirect photodegradation of ofloxacin (OFX) in simulated seawater. Results showed that DOM can significantly accelerate the indirect photodegradation of OFX, and 1 O 2 and 3 DOM * were the main reactive intermediates (RIs) that could promote the indirect photodegradation of OFX. Fluorescence excitation–emission matrix spectroscopy–parallel factor analysis (EEMs-PARAFAC) was used to divide DOM into four fluorescence components. The indirect photodegradation rate of OFX was affected by DOM structure, and terrigenous DOM usually produced more RIs to promote the indirect photodegradation of OFX. Increased salinity significantly promotes the indirect photodegradation of OFX, while increased NO 3 − concentration had no effect on the OFX indirect photodegradation. pH affected the formation of RIs and the structure of OFX, thereby affecting the indirect photodegradation of OFX. The indirect photodegradation rate of OFX increased in the HCO 3 − solution, which is due to the formation of carbonate radical (CO 3 − ). This study is essential in understanding the role of DOM in OFX indirect photodegradation and providing a novel insight into the fate, removal, and transformation of OFX.

Ocean acidification and warming significantly affect coastal eutrophication and organic pollution: A case study in the Bohai Sea - Yuqiu Wei; Dongsheng Ding; Ting Gu; Yong Xu; Xuemei Sun; Keming Qu; Jun Sun; Zhengguo Cui (Marine Pollution Bulletin, 2023)

Exploring the key factors affecting the seasonal variation of phytoplankton in the coastal Yellow Sea - Yingzhe Wang; Ying Liu; Xueyang Chen; Zhengguo Cui; Keming Qu; Yuqiu Wei (Frontiers in Marine Science, 2022)
Marine phytoplankton play crucial roles in the ocean’s biological pump and have great impacts on global biogeochemical cycles, yet the knowledge of environmental variables controlling their seasonal dynamics needs to be improved further, especially in the coastal ecosystems. In order to explore the determinants affecting the seasonal variation of phytoplankton, here we conducted three surveys during spring, summer and autumn along the coastal Yellow Sea. Among the phytoplankton community, 49 species of diatoms and 9 species of dinoflagellates were observed in spring, 63 species of diatoms and 10 species of dinoflagellates in summer, and 62 species of diatoms and 11 species of dinoflagellates in autumn. These results thus suggested that there were obvious differences in the number of species across the three seasons, of which diatoms were the most diverse group, followed by dinoflagellates. Additionally, diatoms were the most dominant species of the phytoplankton community and varied largely during different seasons. According to the redundancy analysis, the abundance of phytoplankton community was mainly related to water temperature and dissolved inorganic nitrogen (DIN) during the three seasons, indicating that water temperature and DIN could be the key factors controlling the seasonal variability of phytoplankton community along the coastal Yellow Sea. Also, significant correlations were observed between phytoplankton abundance and heavy metals Zn, As, and Hg during the three seasons, suggesting that these metals also had potential influences on the seasonal dynamics of phytoplankton community in the coastal Yellow Sea.

Ecological risk assessment of metallic nanoparticles on the marine environments: Species sensitivity distributions analysis - Sulan Feng; Lin Zhu; Xinguo Zhao; Qi Sui; Xuemei Sun; Bijuan Chen; Keming Qu; Bin Xia (Frontiers in Marine Science, 2022)
Metallic nanoparticles (NPs) are increasingly being used and inevitably entering the marine environment. Therefore, the adverse effects of NPs on individual marine species have attracted increasing attentions. However, to date, the ecological risks of NPs on the marine ecosystem remain poorly understood. In this study, species sensitivity distributions (SSDs) were constructed for Ag, ZnO, CuO, and TiO 2 NPs to understand their ecotoxicity to the marine ecosystem and the contribution of size effect and ion effect to the nanotoxicity. Furthermore, a case study on the assessment of marine ecological risk and marine environment carrying capacity of metallic NPs was performed in Jiaozhou Bay, China. The results showed the toxicity of metallic NPs to marine species following the order of Ag > ZnO > CuO > TiO 2 . Both size effect and ion effect contributed to the toxicity of NPs. Environmental concentrations of Ag, ZnO, CuO, and TiO 2 NPs are much lower than the predicted no-effect concentrations, indicating that these metallic NPs have not yet posed risks to the marine ecosystem based on currently limited measured environmental concentrations of metallic NPs in seawater. And the marine environment carrying capacity of Ag, ZnO, CuO, and TiO 2 NPs in Jiaozhou Bay seawater were determined to be 5.03, 8.72, 93.06, and 629.79 t, respectively. The results help us understand the ecological risk of NPs in marine environments and provide a scientific basis for the sustainable development of nanotechnology.

Mussel Byssal Attachment Weakened by Anthropogenic Noise - Xinguo Zhao; Shuge Sun; Wei Shi; Xuemei Sun; Yan Zhang; Lin Zhu; Qi Sui; Bin Xia; Keming Qu; Bijuan Chen; Guangxu Liu (Frontiers in Marine Science, 2021)
The increasing underwater noise generated by anthropogenic activities has been widely recognized as a significant and pervasive pollution in the marine environment. Marine mussels are a family of sessile bivalves that attach to solid surfaces via the byssal threads. They are widely distributed along worldwide coastal areas and are of great ecological and socio-economic importance. Studies found that anthropogenic noise negatively affected many biological processes and/or functions of marine organisms. However, to date, the potential impacts of anthropogenic noise on mussel byssal attachment remain unknown. Here, the thick shell mussels Mytilus coruscus were exposed to an ambient underwater condition (∼50 dB re 1 μPa) or the playbacks of pile-driving noise (∼70 or ∼100 dB re 1 μPa) for 10 days. Results showed that the noise significantly reduced the secretion of byssal threads (e.g., diameter and volume) and weakened their mechanical performances (e.g., strength, extensibility, breaking stress, toughness and failure location), leading to a 16.95–44.50% decrease in mussel byssal attachment strength. The noise also significantly down-regulated the genes expressions of seven structural proteins (e.g., mfp-1, mfp-2, mfp-3, mfp-6, preCOL-P, preCOL-NG, and preCOL-D) of byssal threads, probably mediating the weakened byssal attachment. Given the essential functions of strong byssal attachment, the findings demonstrate that the increasing underwater anthropogenic noise are posing a great threat to mussel population, mussel-bed community and mussel aquaculture industry. We thus suggest that future work is required to deepen our understanding of the impacts of anthropogenic noise on marine invertebrates, especially these with limited locomotion ability, like bivalves.

Environmental factors affecting regional differences and decadal variations in the buried flux of marine organic carbon in eastern shelf sea areas of China - Qian Yang; Keming Qu; Shu Yang; Yao Sun; Yan Zhang; Mingying Zhou (Acta Oceanologica Sinica, 2021)

Selective feeding of bay scallop Argopecten irradians on phytoplankton community revealed by HPLC analysis of phytopigments in Bohai Sea, China - Tao Jiang; Longhua Wang; Fuchong Zhang; Xiao Fang; Lin Lu; Jihong Zhang; Wei Wang; Keming Qu; Chao Chai (Journal of Oceanology and Limnology, 2019)

Coccolithophore responses to the Pacific Decadal Oscillation in the East China Sea region of the Northwest Pacific from ad 1901 to 2013 - Shu Yang; Mingli Yuan; Qian Yang; Jiansheng Huang; Mengran Sun; Jun Sun; Keming Qu; Yao Sun (Journal of Quaternary Science, 2019)
A high‐resolution study of coccolithophores in a sediment core from the East China Sea (ECS) region of the Northwest Pacific revealed that fluctuations in coccolithophore assemblages responded well to the Pacific Decadal Oscillation (PDO) during 1901–2013. Emiliania huxleyi and Gephyrocapsa oceanica were the most dominant species, accounting for more than 97% of all the ten detected species. The variation of the two dominant species showed a significant positive correlation, and they both increased during peak values of the PDO. Decreased stratification and increased nutrient supplementation from the bottom water induced by lower sea surface temperatures in the ECS, which were associated with high PDO values, were responsible for the dominant coccolithophore increase. Similarly, the increase of Calcidiscus leptoporus also corresponded to low‐temperature and high‐nutrient conditions associated with the cold phase in the ECS (positive phase of the PDO). The responses of decadal C. leptoporus variations to changes in cold and warm phases of the PDO in the Northwest and Northeast Pacific indicate that C. leptoporus preserved in sediment cores represents a potential indicator for reconstructing phase changes of the PDO during ancient times.

Succession of phytoplankton functional groups from spring to early summer in the central Bohai Sea using HPLC–CHEMTAX approaches - Lin Lu; Tao Jiang; Yong Xu; Yaoyang Zheng; Bijuan Chen; Zhengguo Cui; Keming Qu (Journal of Oceanography, 2018)

A novel approach to evaluate potential risk of organic enrichment in marine aquaculture farms: a case study in Sanggou Bay - Shu Yang; Qian Yang; Xianli Song; Sai Liu; Keming Qu; Yao Sun (Environmental Science and Pollution Research, 2018)

Effects of plant coverage on shrub fertile islands in the Upper Minjiang River Valley - Laiye Qu; Zhongbin Wang; Yuanyuan Huang; Yuxin Zhang; Chengjun Song; Keming Ma (Science China Life Sciences, 2018)

Burial fluxes and sources of organic carbon in sediments of the central Yellow Sea mud area over the past 200 years - Shu Yang; Qian Yang; Sai Liu; Deling Cai; Keming Qu; Yao Sun (Acta Oceanologica Sinica, 2015)

Carbon and nitrogen isotopes analysis and sources of organic matter in surface sediments from the Sanggou Bay and its adjacent areas, China - Bin Xia; Yi Cui; Bijuan Chen; Zhengguo Cui; Keming Qu; Feifei Ma (Acta Oceanologica Sinica, 2014)

Soil microbial properties under different vegetation types on Mountain Han - Miao Wang; LaiYe Qu; KeMing Ma; Xiu Yuan (Science China Life Sciences, 2013)